An Ammonia Removal for Red Craw Crayfi sh Nursery Water Pond by using Electrocoagulation Method - Patcharaprakiti, Nopporn; Sealao, Jeerawan (Food Agricultural Sciences and Technology, 2019)
This paper propose the method of ammonia removal of red craw crayfi sh nursery water pond. The ammonia in water pond has caused from red craw crayfi sh waste which effect to baby red craw crayfi sh to have strain, anorexia, slow growth and may die. Normally, the ammonia in aquaculture water has been founded in form of unionized form (NH3 ) and ionized form (NH4 + ) which can measured by electrode sensor and transform in ammonia intensity (mg/L). The nursery pond system should be control ammonia in water less than 0.01 mg/L for safety and high growth condition. In this paper, the electrocoagulation method which based on electrochemistry principle is presented for ammonia removal. The two of aluminum electrodes are used to be an anode and cathode which receive direct current positive and negative to electrode respectively. An oxidation-reduction (redox) reaction has impact to aluminum ion separation, fl occulation, fl oatation and sedimentation with ammonia particle. The input parameter of this reaction such as types of electrodes, area of electrodes (cm2 ), voltage level (V), magnitude of current (A) and current density (A/cm2 ) are studied. The output parameters of reaction such as TDS (Total Dissolved Solid), EC (Electrical Conductivity), pH and ammonia intensity are focused. The economic aspect is concerned in term of energy cost and corrosion of aluminum material quantity. The result found that electrocoagulation method can remove ammonia intensity from from 1.8 mg/L to 0.8 in 30 minutes and 0.8 mg/L to 0.05 mg/L in 30 minutes for 10 liters reactor chamber by using energy consumption 3.75 kWh/m3 or 15 bath/m3